String Instruments: Bowed - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear world-class performances on bowed string instruments - - Discover the erhu, a bowed string instrument from China - - Enjoy some country fiddling - - See and hear an extraordinary young violinist perform at ages 3, 9, and 12 - - See performances by famous virtuosi.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - Information about the Performers - - Correlations with THE MUSIC CONNECTION - - Questions to Encourage Critical Thinking - - Student Follow-up - - Vocabulary - - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Bowed stringed instruments; Musical instruments; Films for the hearing impaired